2018
DOI: 10.1016/j.jcmg.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of FFR Derived From Coronary CT Angiography With SPECT Perfusion Imaging in Stable Coronary Artery Disease

Abstract: In patients with stable chest pain and CAD as determined by coronary CTA, the overall diagnostic accuracy levels of FFR and SPECT were identical in assessing hemodynamically significant stenosis. However, FFR demonstrated a significantly higher diagnostic sensitivity than SPECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 34 publications
0
55
0
1
Order By: Relevance
“…There is high per-patient and per-vessel agreement between FFR CT and invasive FFR using the threshold of 0.80 for both techniques (1,(15)(16)(17)(18). An FFR CT value greater than 0.80 indicates that the lesion is unlikely to be hemodynamically Abbreviations CAD = coronary artery disease, FFR = fractional flow reserve, FFR CT = CT angiography-derived FFR, LAD = left anterior descending artery, SCCT = Society of Cardiovascular Computed Tomography Summary Expert opinion and recommendation was given by an independent group of physicians on a standardized interpretation and reporting approach for CT-derived fractional flow reserve testing supported by years of clinical experience.…”
Section: Ffr Ct Thresholdmentioning
confidence: 97%
See 3 more Smart Citations
“…There is high per-patient and per-vessel agreement between FFR CT and invasive FFR using the threshold of 0.80 for both techniques (1,(15)(16)(17)(18). An FFR CT value greater than 0.80 indicates that the lesion is unlikely to be hemodynamically Abbreviations CAD = coronary artery disease, FFR = fractional flow reserve, FFR CT = CT angiography-derived FFR, LAD = left anterior descending artery, SCCT = Society of Cardiovascular Computed Tomography Summary Expert opinion and recommendation was given by an independent group of physicians on a standardized interpretation and reporting approach for CT-derived fractional flow reserve testing supported by years of clinical experience.…”
Section: Ffr Ct Thresholdmentioning
confidence: 97%
“…Accordingly, in vessels that have been assessed using both techniques, if the measurement locations of invasive FFR and FFR CT are not matched, their values can be different and may not closely correlate. significant and that the patient can be safely treated with optimal medical treatment without further downstream testing (1,(12)(13)(14)(15)(16)(17)(18)22,23). A poststenotic FFR CT value less than or equal to 0.80 indicates the possibility of hemodynamic significance (1,(15)(16)(17)(18).…”
Section: Ffr Versus Ffr Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, only two-thirds of the patients to whom revascularization was exposure. [25][26][27] FFRCT may provide advantages in each of these areas, because of its accuracy 6-8 and elimination of additional visits and radiation exposure. Our analysis demonstrated that the proportion of patients deemed to require additional testing in Japan, at nearly 45% following the initial assessment by cCTA, was reduced to nearly zero (0.02%) after FFRCT analysis.…”
Section: Ffrct Reduced Additional Testing and Stratified Patientsmentioning
confidence: 99%